CRISPR-Cas gene perturbation and editing in human induced pluripotent stem cells - van Essen, M; Riepsaame, J; Jacob, J (Mary Ann Liebert, 2021)
Directing the fates of human pluripotent stem cells (hPSC) to generate a multitude of differentiated cell types allows the study of the genetic regulation of human development and disease. The translational potential of hPSC is maximized by exploiting CRISPR to silence or activate genes with spatial and temporal precision permanently or reversibly. Here, we summarize the increasingly refined and diverse CRISPR toolkit for the latter forms of gene perturbation in hPSC and their downstream applications. We discuss newer methods to install edits efficiently with single nucleotide resolution and describe pooled CRISPR screens as a powerful means of unbiased discovery of genes associated with a phenotype of interest. Last, we discuss the potential of these combined technologies in the treatment of hitherto intractable human diseases and the challenges to their implementation in the clinic.